IDENTIFIKASI MOLEKULER BAKTERI SIMBION SPONS LAUT HALICLONA (REINERA) SP. SEBAGAI ANTIBAKTERI - Pahriyani, Ani; Haq, Fitriana Mifthahul; Wahyudi, Priyo (Jurnal Farmasi Indonesia, 2019)
Bacterial symbiont known to be able to produce secondary metabolites, that it?s utilization as the source of bioactive compounds is increase. Study of Mulyaningsih (2016) has reported that the bacterial symbiont of sponge Spheciospongia inconstans from Harapan Island, Kepulauan Seribu has a potentcy to produce antibacterial compounds. The aim of this study was to identify species of symbiont bacterial isolates of sponge of Spheciospongia inconstans which can produce antibacterial substance based on  16S  rRNA  gene.  Total  DNA of the five bacterial isolates from previous study were isolated using Wizard Genomic DNA Purification Kit, then amplified the 16S rRNA gene using primers 27f and 1492r. The amplification results were sequenced and aligned using BLAST program. The results of this study only succeeded in identifying isolate 6FS3 of bacterial symbiont that had an 100% similarity with bacteria Bacillus thermophilus strain Sgz-10.